Ultrasonic Welding of Thermoplastic Composites - Villegas, Irene Fernandez (Frontiers in Materials, 2019)
Ultrasonic welding is a very fast and energy-efficient technique for the joining of thermoplastic composites. This article looks into main aspects of ultrasonic welding of thermoplastic composites, namely energy directors, process parameters, in situ process monitoring, welding of dissimilar composite materials and upscaling routes. From the viewpoint of the author of this paper, these are key topics for deepening our insight into the ultrasonic welding process and, eventually, for enabling its future industrialization.